HUBUNGAN KEPERCAYAAN DIRI DAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Eneng Eni Zahrotul Aeni; Irma Nurfahriani; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research aims to examine how the correlation of self-confidence to the ability of mathematical reasoning of Junior High School student. The type of research used is correlational research. The subject of research is the students of class IX SMP Negeri 2 Ngamprah. Data collection techniques in this research is a test of mathematical reasoning ability in the form of description and self-confidence questionnaire. The results of the indicate a significant relationship between self-confidence and mathematical reasoning ability of junior high school students.